2014
DOI: 10.1371/journal.pone.0100613
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Approach to the Analysis of Subset-Specific Responses to Lipopolysaccharide in Dendritic Cells

Abstract: Dendritic cells (DCs) are critical for regulating CD4 and CD8 T cell immunity, controlling Th1, Th2, and Th17 commitment, generating inducible Tregs, and mediating tolerance. It is believed that distinct DC subsets have evolved to control these different immune outcomes. However, how DC subsets mount different responses to inflammatory and/or tolerogenic signals in order to accomplish their divergent functions remains unclear. Lipopolysaccharide (LPS) provides an excellent model for investigating responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Patients with high DC expression show worse prognosis than patients with low DC expression in HCC. DCs are regarded as crucial regulators of T-cell responses and involved in pathology via activating T cells and B cells ( Hancock and et al, 2014 ; van Uden et al, 2019 ). Plasmacytoid dendritic cells (pDCs) have been documented in multiple primary and metastatic human cancers ( Vermi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high DC expression show worse prognosis than patients with low DC expression in HCC. DCs are regarded as crucial regulators of T-cell responses and involved in pathology via activating T cells and B cells ( Hancock and et al, 2014 ; van Uden et al, 2019 ). Plasmacytoid dendritic cells (pDCs) have been documented in multiple primary and metastatic human cancers ( Vermi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…differences in respiratory tract pathogen load and in exposure to antigens causing hypersensitivity reactions may elicit different pathogenic pathways. In this context it is intriguing that in a systems biology study of LPS stimulation of dendritic cell subpopulations, two of the genes within the region on chromosome 19 of interest, namely PLD3 and SERTAD1, have been found to be selectively regulated in CD11b and CD8 dendritic cell subpopulations, respectively, which are distinct dendritic cell populations that regulate Th2 and Th1 immune responses, respectively 31 . Thus, one might argue that the apparent contradiction of opposite risk alleles might be due to differences in pathogenic pathways caused by different environmental factors in Finnish vs. British children although the ultimate result is similar in terms of prolonged middle ear effusion characteristic of COME.…”
Section: Discussionmentioning
confidence: 99%
“…None of our genes are included in gene categories that are enriched in previously suggested genes associated with OM, implying that a gene in this region may contribute to OM pathogenesis through a novel mechanism. Nevertheless, it is quite plausible that a gene, like PLD3 or SERTAD1 or both, that is highly up-regulated upon stimulation by pathogens and that is specifically regulated in dendritic cell subsets that control distinct immune response types 31 would be a relevant candidate gene for OM.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide microarray analyses have identified several apoptotic regulators, including Bim and GILZ, in the regulation of GC-induced apoptosis [reviewed in 47 ]. A recent study comparing subset-specific transcriptomes of murine splenic CD8 + and CD11b + DC subsets found that at steady state, CD8 + DCs had 3- to 26-fold higher levels of transcripts encoding the proapoptotic genes Bad , Bim , and BCL2l14 ( BclG ) [ 48 ]. Moreover, 24 hr after LPS challenge mRNA encoding the anti-apoptotic Bcl-xL was 20-fold lower in CD8 + compared to CD11b + DCs.…”
Section: Discussionmentioning
confidence: 99%